Alpha-synuclein in cutaneous small nerve fibers - Siepmann T; Illigens BM; Barlinn K (Neuropsychiatric Disease and Treatment)
Timo Siepmann,1 Ben Min-Woo Illigens,2 Kristian Barlinn1 1Department of Neurology, University Hospital Carl Gustav Carus, Technische Universität Dresden, Dresden, Germany; 2Department of Neurology, Beth Israel Deaconess Medical Center, Harvard Medical School, Boston, MA, USA Abstract: Despite progression in the development of pharmacological therapy, treatment of alpha synucleinopathies, such as Parkinson’s disease (PD) and some atypical parkinsonism syndromes, is still challenging. To date, our knowledge of the mechanisms whereby the pathological form of alpha-synuclein causes structural and functional damage to the nervous system is limited and, consequently, there is a lack of specific diagnostic tools to evaluate pathology in these patients and differentiate PD from other neurodegenerative proteinopathies. Recent studies indicated that alpha-synuclein deposition in cutaneous small nerve fibers assessed by skin biopsies might be a valid disease marker of PD and facilitate early differentiation of PD from atypical parkinsonism syndromes. This observation is relevant since early diagnosis may enable timely treatment and improve quality of life. However, challenges include the necessity of standardizing immunohistochemical analysis techniques and the identification of potential distinct patterns of intraneural alpha-synuclein deposition among synucleinopathies. In this perspective, we explore the scientific and clinical opportunities arising from alpha-synuclein assessment using skin biopsies. These include elucidation of the peripheral nervous system pathology of PD and other synucleinopathies, identification of novel targets to study response to neuroprotective treatment, and improvement of clinical management. Furthermore, we discuss future challenges in exploring the diagnostic value of skin biopsy assessment for alpha-synuclein deposition and implementing the technique in clinical practice. Keywords: Parkinson’s disease, diagnosis, skin, immunohistochemistry, biopsy